PENGARUH ETHICAL IDEOLOGY TERHADAP ETHICAL JUDGEMENTS PADA MAHASISWA AKUNTANSI - Aziz, Abdul; Cahyonowati, Nur (Diponegoro Journal of Accounting, 2015)
Ethical judgement is the process by which an individual determines that one of the alternatives is morally right and the other alternative is morally wrong. This capability is very important and needed by each individual in performing their duties. This study aims to analyze the effect of ethical ideology towards ethical judgments, ethical ideology consist of idealism and relativism. This study was conducted in 2015. The data was collected using a questionnaire. The population of this study were students Accounting Profession in Semarang city and the sample using simple random sampling technique. The analysis technique used is multiple linear regression and the Kruskal-Wallis test. Statistical analysis showed that idealism and relativism has significant effect on ethical judgments. The results indicate that the ethical ideology have a significant effect on ethical judgments, where idealism has a positive significant and relativism has a negative significant. And it is known that the group absolutist judge stricter than the other groups.